2017
DOI: 10.1021/acschembio.7b00419
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin Biosynthesis via Transient Cytidylylation of 2-Hydroxyethylphosphonate by the Bifunctional Fom1 Enzyme

Abstract: Fosfomycin is a wide-spectrum phosphonate antibiotic that is used clinically to treat cystitis, tympanitis, etc. Its biosynthesis starts with the formation of a carbon-phosphorus bond catalyzed by the phosphoenolpyruvate phosphomutase Fom1. We identified an additional cytidylyltransferase (CyTase) domain at the Fom1 N-terminus in addition to the phosphoenolpyruvate phosphomutase domain at the Fom1 C-terminus. Here, we demonstrate that Fom1 is bifunctional and that the Fom1 CyTase domain catalyzes the cytidylyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Recent studies by Cho et al revealed that Fom1 from Streptomyces wedmorensis is bifunctional, containing a cytidyltransferase domain in addition to its PEP mutase domain, and that it converts HEP to cytidylyl-2-hydroxyethylphosphonate (HEP-CMP). 4 Further, a recent report in Biochemistry by Sato et al, which is the focus of this Viewpoint, revealed HEP-CMP to be the true substrate for Fom3. 3 After methylation of HEP-CMP to generate cytidylyl-2-hydroxypropylphosphonate (HPP-CMP), it is hypothesized, but not yet confirmed, that FomD, whose function was previously unknown, hydrolyzes HPP-CMP to generate ( S )-HPP, which is then converted to fosfomycin by the nonheme-iron peroxidase Fom4 (Scheme 1).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Recent studies by Cho et al revealed that Fom1 from Streptomyces wedmorensis is bifunctional, containing a cytidyltransferase domain in addition to its PEP mutase domain, and that it converts HEP to cytidylyl-2-hydroxyethylphosphonate (HEP-CMP). 4 Further, a recent report in Biochemistry by Sato et al, which is the focus of this Viewpoint, revealed HEP-CMP to be the true substrate for Fom3. 3 After methylation of HEP-CMP to generate cytidylyl-2-hydroxypropylphosphonate (HPP-CMP), it is hypothesized, but not yet confirmed, that FomD, whose function was previously unknown, hydrolyzes HPP-CMP to generate ( S )-HPP, which is then converted to fosfomycin by the nonheme-iron peroxidase Fom4 (Scheme 1).…”
mentioning
confidence: 85%
“…3 After methylation of HEP-CMP to generate cytidylyl-2-hydroxypropylphosphonate (HPP-CMP), it is hypothesized, but not yet confirmed, that FomD, whose function was previously unknown, hydrolyzes HPP-CMP to generate ( S )-HPP, which is then converted to fosfomycin by the nonheme-iron peroxidase Fom4 (Scheme 1). 4 …”
mentioning
confidence: 99%
“…The biosynthesis of fosfomycin in Streptomyces consists of seven chemical steps. 63,64 Heterologous expression and genetic inactivation experiments indicated that the gene cluster is composed of fom1-4 and fomA-D. 65 Most of these steps (Fig. 5) have been reconstituted and characterized in vitro.…”
Section: Biosynthesis Of Fosfomycin In Streptomycesmentioning
confidence: 99%
“…65,66 However, Fom1 is a bifunctional PepM which is CyTase-fused and identied only in the gene cluster of fosfomycin (1a) from Streptomyces strains. 63 8.1.2 The conversion of 2-HEP to HEP-CMP. This step was not proposed and conrmed until the cytidylyltransferase (CyTase) domain in Fom1 was characterized.…”
Section: Biosynthesis Of Fosfomycin In Streptomycesmentioning
confidence: 99%
See 1 more Smart Citation